Delayed skin reactions to cytoplasmic extracts of Nocardia organisms as a means of diagnosis and epidemiological study of Nocardia infection - Ortiz-Ortiz, L. (1972)
Purified cytoplasmic extracts were prepared from Nocardia asteroides and Nocardia brasiliensis micro-organisms. They contained protein, carbohydrate and nucleic acid material. When these extracts were utilized as skin test antigens in individuals infected with Nocardia, a delayed hypersensitivity reaction was observed. Cross reactivity occurred between the Nocardia antigens, but the inflammatory reaction was usually larger with extracts obtained from the infecting micro-organism. On the other hand, low reactivity, if any, was observed when the same antigens were assayed in patients with tuberculosis and leprosy or in healthy individuals. In addition, the cytoplasmic extract from N. brasiliensis appeared useful in epidemiological studies, since skin reactivity was shown by individuals working or living in areas in which N. brasiliensis was isolated from the soil.